Penerapan Metode "Guided Teaching" Dalam Pembelajaran Kooperatif Guna Meningkatkan Prestasi Belajar Ekonomi Siswa SMKN 2 Madiun - Jatiman, Jatiman (Jurnal Pendidikan, 2010)
This research serves objectives as: 1) to identify whether Guided Teaching technique able to upgrade the studentsâ achievement. 2) to depict the process of teaching and learning under Guided Teaching technique. 3) to describe the teachers efforts to upgrade the studentsâ achievement under Guided Teaching technique.This research os carried out under the classroom action research design, with 34 students of grade XII PJ 1 as the research subjects. The 2 cycles design of this research is attempted to reach 7.5 of the threshold level with 75% of minimal class learning achievement.The first cycle result average score of 63.97 by 52.94% of minimal class learning achievement; where the threshold level is not yet achieved. The second cycle recover the score by 78.82 with 82.35% minimal class learning achievement. Out of the mentioned results, there are also qualitative outcomes which stated as follows: learning activity, class interaction, sharing of knowledge between and among students are encouraged under Guided Teaching Method; recommending that the method significantly makes up the studentsâ achievement quanitatively and qualitatively.Key words: Method, Guided Teaching, Cooperative Learning, Economics